Fish kept within trays full of ice for preservation - Mumbai Archive Project Team (Jio Institute, 2024)
From the moment they are offloaded, fish can be kept fresh with the use of ice. Ice factories, typically found near the fish market, regularly manufacture large amounts of ice for commercial use.